On the well-posedness for the nonlinear radial Schrödinger equation with spatial variable coefficients. (May 2019) - Zheng, Bo-wen
Abstract: In this paper, we study the Cauchy problem for a generalized nonlinear Schrödinger equation with spatial variable coefficients. A new weighted Sobolev space W 1, q ( R + ) is introduced and the range of admissible pairs for the Strichartz estimates is improved. As an application, we show the local well-posedness result for the initial data in W 1, q ( R + ) .